Pump users handbook - Rayner, R.
This handbook places emphasis on the importance of correct interpretation of pumping requirements, both by the user and the supplier. Completely reworked to incorporate the very latest in pumping technology, this practical handbook will enable you to understand the principles of pumping, hydraulics and fluids and define the various criteria necessary for pump and ancillary selection. The Pump Users Handbook will prove an invaluable aid in ordering pump equipment and in the recognition of fundamental oprational problems.